2012
DOI: 10.1007/s00037-012-0039-3
|View full text |Cite
|
Sign up to set email alerts
|

Bounded-Depth Circuits Cannot Sample Good Codes

Abstract: Abstract. We study a variant of the classical circuit-lower-bound problems: proving lower bounds for sampling distributions given random bits. We prove a lower bound of 1 − 1/n Ω(1) on the statistical distance between (i) the output distribution of any small constant-depth (a.k.a. AC 0 ) circuit f : {0, 1} poly(n) → {0, 1} n , and (ii) the uniform distribution over any code C ⊆ {0, 1} n that is "good", i.e. has relative distance and rate both Ω(1). This seems to be the first lower bound of this kind. We give t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…Last, the main body in [ASTS + 03] studies a bounded-error generation, and showed an exponential separation (O(log n) versus Ω( √ n)), while ours aims to generate the exact target correlation, and showed an "infinite" separation (1 versus log 2 n unconditionally, and 1 versus n assuming a conjecture). Studies of computational issues of probabilistic distributions instead of Boolean functions has recently be advocated by Viola [Vio10,LV10]. It is our hope that studies of the correlation complexity of distributions later help to sharpen our understandings of various complexity questions for Boolean functions.…”
Section: More Related Workmentioning
confidence: 99%
“…Last, the main body in [ASTS + 03] studies a bounded-error generation, and showed an exponential separation (O(log n) versus Ω( √ n)), while ours aims to generate the exact target correlation, and showed an "infinite" separation (1 versus log 2 n unconditionally, and 1 versus n assuming a conjecture). Studies of computational issues of probabilistic distributions instead of Boolean functions has recently be advocated by Viola [Vio10,LV10]. It is our hope that studies of the correlation complexity of distributions later help to sharpen our understandings of various complexity questions for Boolean functions.…”
Section: More Related Workmentioning
confidence: 99%
“…It follows immediately from bounds on the noise-sensitivity of small AC 0 circuits [20,6] that small AC 0 circuits cannot compute good codes. This result was generalized in [32,21] (cf. [5]).…”
Section: Introductionmentioning
confidence: 75%
“…We were not able to do so, and we raise this as another challenge. (Some recent progress on this question appears in [LV10]. )…”
Section: Definition 12 a Function F : {0 1} → {0 1}mentioning
confidence: 99%
“…Recently, Lovett and the author [LV10] prove that small AC 0 circuits cannot generate the uniform distribution over any good error-correcting codes. This result does not solve Challenge 1.1 -it does not apply to distributions like (X, b(X)) -although it does answer a question asked in a preliminary version of this work.…”
Section: Definition 12 a Function F : {0 1} → {0 1}mentioning
confidence: 99%